The perceived responsiveness of laws and policies addressing the social concerns, needs and problems of South Korean students undertaking a non-degree course in the city of Iloilo - Abastillas, Cristine Joy
This study examines the perceived responsiveness of laws and policy addressing the social concerns, needs and problems of South Korean students undertaking a non-degree course int he city of Iloilo. It delves into the laws and policy that govern these alien students namely, the Office Memorandum Order No. 00-57 derived from the Philippine Immigration Act of 1940 and the Revised Penal Code of the Philippines. The subjects of this study are South Korean students taking a non-degree English language course in fourteen tutorial centers located in the city of Iloilo. Moreover, tutors employed in the said English language schools are as well interviewed to confirm some issues that South Korean students experience in their temporary sojourn in the city. The involvement of the Bureau of Immigration Officer-in-Charge and the Iloilo City Legal Counsel Official as key informants were also critical in gathering some data pertinent to the concerns faced by South Korean students as they provide profound information with a touch of legality . This study found out that the laws and policy identified and examined in this study partially address the social concerns, needs and problems of alien students in Iloilo City. The Penal Code only addresses aliens' safety concerns and problems, while the Immigration Act, on the other hand, solely addresses the matters relating to immigration procedures and requirements which includes the acquisition of Special Study Permit. These two laws were found to have gaps since they do not address all the social concerns, needs and problems of South Korean students perceived by the interviewees. The social concerns, needs and problems of South Korean students in the city are not addressed because of the non-specificity of the two laws and the policy examined. Nonetheless, there still exist other domestic statutes and pronouncements that can address the concerns and problems of these alien students. Unfortunately, these laws are already outside the scope of this research project. Therefore, it is recommended that other laws be analyzed so as to know whether they effectively respond to the other social concerns, needs and problems of South Korean non-degree course students or not.